PENGARUH KINERJA TERHADAP KEPUASAN MASYARAKAT PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA - LUMI, JACKLIN; OGOTAN, MARTHA; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2018)
The problem in this study is the service performance towards community satisfaction, service performance builds standards in all services to be provided more and determined by the community. Community satisfaction is the main factor that must be considered. The method used in this study is a quantitative research method using a simple linear regression equation, correlation analysis. The purpose of this study is to Based on the limitation of the problem, then the formulation of the problem in this study is: Is there any effect of performance on community satisfaction on the Minahasa District Population and Civil Registration Service?, the method used in this research is quantitative research methods. By using a simple linear regression formula, correlation analysis is a correlation coefficient and t test statistics to test the significance of the correlation coefficient. Where to get the author's data using a questionnaire circulated to all respondents to be sampled.In this study there were 60 people divided into 30 respondents X variables and 30 variable respondents Y at the Minahasa District Civil Registration Office. With the formulation of the problem: (1) The extent of the influence of performance in the Population and Civil Registration Service on the satisfaction of the Minahasa District community, (2) The degree of relationship and determination power between the performance in the Population and Civil Registration Service with the satisfaction of the Minahasa District community.Based on the results of the analysis obtained Y Ì‚ == 20.27 + 0.6727 X. These results indicate that the variable X is Service Performance with Y variable that is Community Satisfaction, besides that also after being analyzed using the correlation coefficient formula, there is a strong relationship between service performance and community satisfaction in the Office of the Population and Civil Registration Office of Minahasa Regency with a value of 0 , 5152. From the results of research at the OfficeKeyword: Service Performance Community Satisfaction